The Transition of Medical Education from Traditional to Lifelong Learning and Its Impact on Health Care Providers: A Review Article - Zinab Elfituri,; Abir Sharif , (AlQalam Journal of Medical and Applied Sciences, 2023)
Lifelong learning is a concept that has been recognized by governments and educational institutions worldwide as essential to keeping pace with the rapidly changing world. In the field of medicine, continuous professional development (CPD) is an integral part of a physician's lifelong learning journey. Over time, the term "Continuing Medical Education" (CME) has replaced CPD, although both terms are used interchangeably. Lifelong learning is considered an integral component of professionalism and practice-based learning and improvement in medical education. Therefore, it is essential for primary care physicians to maintain and improve their clinical knowledge, skills, and attitudes by continuing to learn throughout their careers. This article dives into the history of medical education to identify the evolution and impact of lifelong learning methods